STING directly recruits WIPI2 for autophagosome formation during STING‐induced autophagy - Wan, Wei; Qian, Chuying; Wang, Qian; Li, Jin; Zhang, Hongtao; Wang, Lei; Pu, Maomao; Huang, Yewei; He, Zhengfu; Zhou, Tianhua; Shen, Han‐Ming; Liu, Wei (The EMBO journal, 2023)
The cGAS‐STING pathway plays an important role in host defense by sensing pathogen DNA, inducing type I IFNs, and initiating autophagy. However, the molecular mechanism of autophagosome formation in cGAS‐STING pathway‐induced autophagy is still unclear. Here, we report that STING directly interacts with WIPI2, which is the key protein for LC3 lipidation in autophagy. Binding to WIPI2 is necessary for STING‐induced autophagosome formation but does not affect STING activation and intracellular trafficking. In addition, the specific interaction between STING and the PI3P‐binding motif of WIPI2 leads to the competition of WIPI2 binding between STING and PI3P, and mutual inhibition between STING‐induced autophagy and canonical PI3P‐dependent autophagy. Furthermore, we show that the STING‐WIPI2 interaction is required for the clearance of cytoplasmic DNA and the attenuation of cGAS‐STING signaling. Thus, the direct interaction between STING and WIPI2 enables STING to bypass the canonical upstream machinery to induce LC3 lipidation and autophagosome formation. Synopsis STING‐induced autophagy does not depend on ULK1 complex and PIK3C3 complex. Here, we report that STING directly interacts with WIPI2 and brings WIPI2 to STING‐positive vesicles. Our results reveal a mechanism by which WIPI2 is recruited to phagophore for LC3 lipidation and phagophore expansion during STING‐induced autophagosome formation. STING brings WIPI2 to STING‐positive vesicles for autophagosome formation during STING‐induced autophagy. STING and PI3P competitively bind to WIPI2, which leads to mutual inhibition between STING‐induced autophagy and PI3P‐dependent autophagy. STING‐WIPI2 interaction is required for autophagy‐dependent clearance of cytoplasmic DNA and the attenuation of cGAS‐STING signaling. Graphical Abstract STING interacts with the autophagy protein WIPI2 to promote autophagy‐dependent clearance of cytoplasmic DNA and the attenuation of cGAS‐STING signaling.